Genetics, Breeding and Genetic Engineering to Improve Cottonseed Oil and Protein: A Review - Wu, Man; Pei, Wenfeng; Wedegaertner, Tom; Zhang, Jinfa; Yu, Jiwen (Frontiers in Plant Science, 2022)
Upland cotton (Gossypium hirsutum) is the world’s leading fiber crop and one of the most important oilseed crops. Cotton breeding has primarily focused on fiber yield and quality. However, there is an increased interest and demand for genetic improvements in cottonseed traits, including protein, oil, fatty acid, and amino acids for broad food, feed and biofuel applications. As a byproduct of cotton production, cottonseed is an important source of edible oil in many countries and could also be a vital source of proteins for human comsuption. Genetic variation in cottonseed oil and protein contents exists within the genus of Gossypium and cultivated cotton, despite the fact that many decades of breeding for high yield and better fiber quality have substantially narrowed the natural genetic variation available for effective cottonseed quality improvement within Upland cotton. A plethora of genes and quantitative trait loci (QTLs) associated with cottonseed oil, fatty acids and protein contents have been identified, providing important information for genetic improvement of cottonseed quality. Genetic engineering in cotton through RNA interference and insertions of additional genes of other genetic sources, in addition to more recent development of genome editing approaches have been achieved considerable progress in altering the relative levels of protein, oil, fatty acid composition, and amino acids in cottonseed for enhanced nutritional value and expanded industrial applications. The objective of this review is to summarize and discuss the cottonseed oil biosynthetic pathway and major genes involved, genetic basis of cottonseed oil and protein content, genetic engineering, genome editing through CRISPR/Cas9, and QTLs associated with quantity and quality enhancement of cottonseed oil and protein.